Structural Equation Modeling of Factors Affecting Accountability-Based Accounting in Public Sector Entities - Hien, Nguyen Thi Thu; Hai, Phan Hong; Bui, Thi Thu Thao; Tuan, Dang Anh (Emerging Science Journal, 2025)
Objectives: This study aims to identify factors influencing accountability-based accounting and propose a conceptual framework for public-sector accounting to enhance decision-making and accountability. Methods/Analysis: Conducted in Vietnam in 2023, the research employs quantitative analysis of survey data collected from 492 civil servants across 282 public entities, using SmartPLS for structural equation modeling. Findings: There are significant positive correlations between accountability-based accounting and four key factors: accrual-based accounting, felt accountability, information disclosure, and financial report quality. Among these, accrual-based accounting exerts the most substantial direct influence on the use of accounting information for accountability purposes. Felt accountability demonstrates direct and indirect effects, mediating relationships between other factors. The study highlights that effective accountability requires account givers to align with account holders’ needs, legitimacy, and expertise, while accrual-based accounting must prioritize improving user comprehension and usability of information. Novelty/Improvement: Transparency and publicity are critical for ensuring public-sector accounting information is reliable, relevant, and actionable. The proposed framework advances public-sector accounting theory by integrating accountability as a foundational principle, offering practical guidance for policymakers to strengthen accountability mechanisms. This research contributes a novel perspective by empirically validating the interplay of accounting components within an accountability-centric model, providing a basis for future conceptual and regulatory developments in public sector.